2018
DOI: 10.3390/atmos9010032
|View full text |Cite
|
Sign up to set email alerts
|

Decision Science Perspectives on Hurricane Vulnerability: Evidence from the 2010–2012 Atlantic Hurricane Seasons

Abstract: Abstract:Although the field has seen great advances in hurricane prediction and response, the economic toll from hurricanes on U.S. communities continues to rise. We present data from Hurricanes Earl (2010), Irene (2011), Isaac (2012), and Sandy (2012 to show that individual and household decisions contribute to this vulnerability. From phone surveys of residents in communities threatened by impending hurricanes, we identify five decision biases or obstacles that interfere with residents' ability to protect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…Even when residents living in a high-risk area have hurricane shutters, they often do not put them up before the storm hits (Baker et al 2012). Some researchers have found that few people living in evacuation zones plan to evacuate (Milch et al 2018). Even those who plan to evacuate may not ultimately evacuate when the storm approaches (Meyer et al 2014).…”
Section: B Public Reaction To Hurricane Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Even when residents living in a high-risk area have hurricane shutters, they often do not put them up before the storm hits (Baker et al 2012). Some researchers have found that few people living in evacuation zones plan to evacuate (Milch et al 2018). Even those who plan to evacuate may not ultimately evacuate when the storm approaches (Meyer et al 2014).…”
Section: B Public Reaction To Hurricane Informationmentioning
confidence: 99%
“…Single action bias Individuals who are faced with problems that may require multiple protective steps stop preparing after completing just one of those steps (Weber 1997) When faced with a hurricane threat, individuals may take a single preparatory step to ''relieve the psychological burden of inaction'' and then stop (Milch et al 2018); communications might be designed to emphasize that multiple actions are needed for communities in the hurricane's path Temporal/spatial myopia Individuals tend to underestimate the costs of phenomena that are farther away in space and time…”
Section: Loss Aversionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the October 2015 flood event in Columbia, SC, indicated that considerations for public safety were sometimes secondary to profitable land development [21]. Hurricane research that was published in 2018 analyzed the decision biases of persons affected by hurricanes and found that temporal band spatial myopia is a major issue that places a lower priority on long-term decisions (e.g., preparation) than short term routine tasks with the failed intention of addressing the long term need when the disaster event is closer in time [22].…”
Section: Introductionmentioning
confidence: 99%
“…Population density, race/ethnicity, and socio-economic status are key factors that consistently increase social vulnerability. Recent research [23] Hurricane research that was published in 2018 analyzed the decision biases of persons affected by the four specific hurricanes: Earl (2010), Irene (2011), Isaac (2012), and Sandy (2012) highlighted five major decision biases that may put communities at greater risk of damage and deaths from a hurricane [24]. Temporal and spatial myopia is a major issue that places at lower priority long-term decisions such as preparation for a pending hurricane than it does on short term routine tasks with the failed intention of addressing the long term need when the disaster event is closer in time.…”
Section: Introductionmentioning
confidence: 99%